AUTOMATION OF INDUSTRIAL (IOT) AND CYBER SECURITY - Santi Priyanka Prem , V.V.S.S.S.Balaram, Sunil Bhutada (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
our everyday lives, it could be easy to gain personal information or know the information of the individual business network community in order to allow cyber security attacks in our country to collapse and lose control. Cyber attacks are limitless in the IT field or in companies of the network. As a matter of fact, many business industries use IoT that is used to link and pass data from one computer to another that is called MACHINE TO MACHINE communication while the transfer of data cyber security threats are transferred so that the attacker can access and track the data. We have suggested industrial automation using IoT by including cyber security in this article. The key aim of this paper is to allow data protection through the use of IoT in industries and to share or transfer protected messages.